Description of the male and redescription of the female of Agaurella mirabilis (Brunner von Wattenwyl, 1891) (Orthoptera: Tettigoniidae) with new behavioral data - Mendes, Diego Matheus De Mello; Alves-Oliveira, João Rafael (Zootaxa, 2015)
The description of the male of Agaurella miriabilis is provided as well as the redescription of the female with additional characters. It is recorded for the first time the geographical occurence to Brazil, within the states of Amazonas and Rondônia, and behavioral data.